Analisis Efisiensi Penanggulangan Lost Circulation Dengan Metode Konvensional dan Under Balanced Drilling Pada Formasi Kujung Blok Z - Cia, Rifaldy Prasetya; Wiyono, Joko; Suprayitno, Abdi; Battu, Desianto Payung; Karim, Abdul Gafar; Wicaksono, Dwiki Ganang; Restu, Pratama Bagus (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
This study will analyze the efficiency of conventional methods and Unbalanced Drilling (UBD) in addressing lost circulation in Kujung Block Z formation. Lost circulation is one of the major challenges in drilling operations that can lead to operational risks and increased costs. This study compares the effectiveness of the two methods based on operational parameters such as rate of penetration (ROP), drill bit load (WOB) and formation pressure stability. The results of this study show that the UBD method is more effective in suppressing lost circulation compared to conventional methods, especially under extremely low formation pressure conditions.